Studi Kualitatif Potensi, Pemanfaatan, Ancaman Dan Keberhasilan Produksi Kacang Tanah Di Desa Rantau Panyang Timur Kabupaten Aceh Barat - Aulia, Muhammad Reza; Putra, Aulia; Purnama, Endang; Anantama, Arif; Aisyah, Nur (Universitas Katolik Santo Thomas Medan, 2023)
Peanuts are an important food crop with significant economic potential in Rantau Panyang Timur Village, West Aceh Regency, and other regions. Despite its great potential, there are challenges in the utilization and production of peanuts that need to be addressed. Previous research on peanuts has been conducted, but there is a lack of specific studies focusing on the potential, utilization, threats, and success of peanut production in Rantau Panyang Timur Village. This study offers a novel contribution with an in-depth focus on the potential, utilization, threats, and success of peanut production. The research findings indicate that Rantau Panyang Timur Village has good potential for peanut growth, with factors such as suitable climate, fertile soil, and extensive farming experience among farmers. However, there are limitations in the broader utilization of peanuts and product diversification. Peanut production in the village also varies from year to year, influenced by external factors such as unpredictable weather, plant diseases, as well as the limitations in farmers' knowledge and skills. To enhance the growth, utilization, and production of peanuts, efforts are needed to improve the knowledge and skills of farmers, strengthen collaboration between farmers and relevant stakeholders, and enhance access to necessary resources. By addressing the challenges and capitalizing on existing potentials, it is expected that peanut production in Rantau Panyang Timur Village can become more successful and sustainable.